Educational games to engage the un-engagable - Carr, John (2011)
Behavioural, emotional and social difficulties in school-aged children are a significant problem in the UK. Such children represent a difficult challenge for educational institutions. Teachers and experts have said that these children find it almost impossible to stay on task in educational activities for more than a trivial amount of time. Interest in computer games as a medium for learning and other non-entertainment purposes has risen significantly in recent years, in part because they can provide an engaging experience to motivate users. This makes the medium an attractive tool for this demographic. There are many problems however facing designers who would attempt to integrate educational content into a game platform. The issue of effective integration between game and education has long been a problematic issue affecting educational game development. Gameplay aspects can often be overlooked in academic projects. Good educational games should integrate the learning content and game experience, this is something that is particularly difficult to achieve effectively. This thesis details a study to design educational games to aid behavioural emotional and social learning. The methodology attempts to blend good game design principles with educational content in such a way that users can be engaged with both the activity and the educational concepts contained within. Two trials were undertaken in schools with participants suffering from a range of severe behavioural emotional or social problems. The results provide evidence suggesting that, if educational gameplay is achieved, these children can be engaged, not only with the game as an activity, but with the educational content on which it is based. The implications are then explored and the potential of educational gameplay evaluated in context of the wider industry of educational and serious games. While this method of integrating educational content within game platforms is effective, it is difficult to achieve, in many subject areas, perhaps prohibitively so.